Painel II – Concorrência e regulação no sistema financeiro - Zarzur, Cristianne Saccab; Reynolds, Michael; Saintive, Marcelo; Oliveira, Gesner; Gomes, Amaro Luiz de Oliveira; Mello, João Manoel Pinho de; Oliveira, Marcos Cavalcante de; Goldberg, Daniel; Ribeiro, Amadeu; Sicsú, Doutor; et al. (Revista do IBRAC, 2024)
Cristianne Saccab Zarzur .................... 87 Michael Reynolds .................... 87 Marcelo Saintive .................... 100 Gesner Oliveira .................... 110 Amaro Luiz de Oliveira Gomes .................... 134 João Manoel Pinho de Mello .................... 145 Marcos Cavalcante de Oliveira .................... 158 Daniel Goldberg .................... 172 Amadeu Ribeiro .................... 188 Doutor Sicsú .................... 189 Elizabeth Farina ..................... 191 João Manoel Pinho de Mello .................... 192 Conselheiro Prado .................... 194 Mauro Grinberg .................... 196 Doutor Laércio .................... 197 Mauro Grinberg ..................... 200